Bedforms on the submarine flanks of insular volcanoes: New insights gained from high resolution seafloor surveys. Issue 4 (23rd April 2020) - Casalbore, Daniele; Clare, Michael A.; Pope, Ed L.; Quartau, Rui; Bosman, Alessandro; Chiocci, Francesco L.; Romagnoli, Claudia; Santos, Rùben
Abstract: A comparative analysis of bedform fields along the submarine flanks of insular volcanoes, characterized by different morpho‐structural settings, volcanic and meteo‐marine regimes (Vanuatu, Kermadec, Bismark, Madeira and Aeolian archipelagos), is presented here to provide insights on the size distribution, morpho‐dynamic and genesis of such bedforms. Two main types of bedforms are recognized according to their size, location and preconditioning/triggering processes. Small‐scale bedforms have wavelengths of tens to hundreds of metres and wave heights of metres. Because of their small‐size, they are typically not recognizable at water depths greater than 400 m from vessel‐mounted bathymetric surveys. Few examples of small‐scale bedforms are reported from upper volcanic flanks, where steep gradients commonly hinder their formation. Their recognition is mostly limited to the thalweg of shallow and flat‐bottomed channels that carve the insular shelf on slope gradients <15°. Small‐scale bedforms are mostly related to erosional–depositional processes due to sedimentary gravity flows that are often the result of a cascading effect between volcanic and non‐volcanic processes (for example, flood discharges and retrogressive landslides). Large‐scale bedforms occur at all water depths, having wavelengths of hundreds/thousands of metres and wave heights up to few hundreds of metres. The origin of large bedforms is more difficult to ascertain, especially if only bathymetric data are available. Some diagnostic criteria are presented to distinguish between bedforms associated with landslide deposits and those associated with density currents. In this latter case, relevant sediment sources and slope gradients (<8°) are key factors for bedform development. Erosional–depositional bedforms are typically related to eruption‐fed density flows formed during large caldera collapses or to large turbidity flows. Bedforms generated by turbidity flows are often observed in the lower volcanic flanks, where an abrupt decrease of gradients is present, often matching a change from confined to unconfined settings. In summary, this study provides insights to interpret bedforms in modern and ancient marine volcaniclastic settings elsewhere.